INFLUENCE OF THERMAL INCREASING THE STATIC STRENGTH OF ALLOY STEELS (Archive of Conferences, 2022)
The basic operational and technological properties of steel are defined (determined) by the contents of their chemical elements. Elements allow reaching (achieve) necessary hardening of a firm solution. In clause the decision these problems is considered.